Снег Энцелада: роман - Веркин Эдуард Николаевич (2022)
Экземпляры: ЦБ (20230511) / Инвентарный номер: 57687 / Цена: 523.96 / Сис.шифр: 84(2=411.2)6 / Авт.знак: В 32 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44